Microfluidic Cultivation and Laser Tweezers Raman Spectroscopy of E. coli under Antibiotic Stress - Pilát, Zdeněk; Bernatová, Silvie; Ježek, Jan; Kirchhoff, Johanna; Tannert, Astrid; Neugebauer, Ute; Samek, Ota; Zemánek, Pavel (Sensors, 2018)
Analyzing the cells in various body fluids can greatly deepen the understanding of the mechanisms governing the cellular physiology. Due to the variability of physiological and metabolic states, it is important to be able to perform such studies on individual cells. Therefore, we developed an optofluidic system in which we precisely manipulated and monitored individual cells of Escherichia coli. We tested optical micromanipulation in a microfluidic chamber chip by transferring individual bacteria into the chambers. We then subjected the cells in the chambers to antibiotic cefotaxime and we observed the changes by using time-lapse microscopy. Separately, we used laser tweezers Raman spectroscopy (LTRS) in a different micro-chamber chip to manipulate and analyze individual cefotaxime-treated E. coli cells. Additionally, we performed conventional Raman micro-spectroscopic measurements of E. coli cells in a micro-chamber. We found observable changes in the cellular morphology (cell elongation) and in Raman spectra, which were consistent with other recently published observations. The principal component analysis (PCA) of Raman data distinguished between the cefotaxime treated cells and control. We tested the capabilities of the optofluidic system and found it to be a reliable and versatile solution for this class of microbiological experiments.
Keywords: Micromanipulation; Spectrum Analysis, Raman; antibakteriální látky; Ramanova spektroskopie; Principal Component Analysis; Optical Tweezers; optická pinzeta; Lab-On-A-Chip Devices; laboratoř na čipu; Escherichia coli; Anti-Bacterial Agents; analýza hlavních komponent; mikromanipulace